The impact of using functional strength exercises to develop some physical capabilities and enhance the performance of wrestling grips - Tawfeeq Ezzi, T. A. F.; Aziz, F. (Proximus Journal of Sports Science and Physical Education, 2024)
The study's objectives were to prepare functional strength exercises that would improve the research sample's physical capabilities and wrestling grip performance as well as to ascertain the effects of utilizing these exercises to improve the research sample's physical capabilities and grip performance. The researchers used the appropriate strategy to address the research issue because experimentation was a key component of the procedure. The researchers' selection of the sample was one of the most important stages and processes of the investigation. The researchers undoubtedly considered the research sample as soon as they started deciding on the topic and goals of the study. Consequently, a sample of twenty-two wrestlers from the advanced division who werepracticing at the Al-Adhamiya Club's wrestling facility were used for the study. Al-Adhamiya Sports Club wrestlers were purposefully chosen for the competition. This led to an increase in the study sample size to 20 wrestlers, or 90.9% of the total research population. The researchers used anthropometric measures to confirm the sample's homogeneity. The findings demonstrated that functional strength training significantly improved the experimental group's physical capabilities in the wrestlers' physical capabilities tests compared to the control group in the post-test.In the physical capabilities tests among the wrestlers, functional strength exercises also revealed a substantial difference in performance levels between the experimental and control groups in the post-test, favoring the experimental group. Regarding the recommendations, they state that functional strength exercises should be used to improve wrestlers' physical capabilities and that these exercises must replicate the performance of the skill,which includes training the muscles involved in the wrestling grip.